A TonB-dependent transporter is required for secretion of protease PopC across the bacterial outer membrane - Nuria Gómez-Santos (Nature Portfolio, 2019)
TonB-dependent transporters (TBDTs) are outer membrane proteins that import nutrients and bacteriocins in bacteria. Here, Gómez-Santos et al. show that a TBDT is required for secretion of a protease in Myxococcus xanthus, suggesting that some TBDTs may be involved in protein secretion.